2004
DOI: 10.1021/ol049258a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of Polyhydroxylated Near-Infrared Carbocyanine Molecular Probes

Abstract: [reaction: see text] A new near-infrared (NIR) fluorescent molecular probe derived from indocarbocyanine dye and galactose was prepared, and the procedure was optimized. The presence of a nonionic polyhydroxyl moiety between hydrophobic groups enhances solubility and possibly minimizes aggregation in aqueous solutions. The structural framework of this molecule provides multivalent sites for labeling diverse molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
78
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 125 publications
(79 citation statements)
references
References 16 publications
(17 reference statements)
0
78
0
Order By: Relevance
“…The weak signal may account for the omission of the blue-shifted peaks in previous reports of the fluorescence properties of these compounds. [7][8][9][10] Upon conjugation of the symmetrical dye cypate with a peptide, the resulting nonsymmetrical cypate-peptide conjugate 5 exhibited a 45 % increase in the level of the 700-nm emission band (relative to cypate), albeit still lower than the 82 % obtained with 3 and 4. Although the 100-nm blue-shifted emission peak could indicate the elimination of a methine bond from the heptamethine structure, [11] it is unlikely that the emission band at 700 nm resulted from the formation of lower homologues (such as tri-or pentamethines) of cypate or ICG, which typically have similar fluorescence lifetimes of cypate at 800 nm (namely, 0.86 ns in dimethyl sulfoxide, DMSO).…”
mentioning
confidence: 95%
“…The weak signal may account for the omission of the blue-shifted peaks in previous reports of the fluorescence properties of these compounds. [7][8][9][10] Upon conjugation of the symmetrical dye cypate with a peptide, the resulting nonsymmetrical cypate-peptide conjugate 5 exhibited a 45 % increase in the level of the 700-nm emission band (relative to cypate), albeit still lower than the 82 % obtained with 3 and 4. Although the 100-nm blue-shifted emission peak could indicate the elimination of a methine bond from the heptamethine structure, [11] it is unlikely that the emission band at 700 nm resulted from the formation of lower homologues (such as tri-or pentamethines) of cypate or ICG, which typically have similar fluorescence lifetimes of cypate at 800 nm (namely, 0.86 ns in dimethyl sulfoxide, DMSO).…”
mentioning
confidence: 95%
“…Large stokes shift could help to reduce self-quenching and measurement error by excitation light and scattered light. 20 The fluorescence quantum yield of six dyes was in the region 0.0001-0.0781 in different solvents. From Table 1 it could be found that the order of fluorescence quantum yield was 3a, 3b > 3c, 3d.…”
Section: Synthesismentioning
confidence: 98%
“…The Stokes' shift was larger than common fluorophores such as fluorescein, rhodamine, and BODIPY, as well as cyanine dyes, which is desirable for suppressing self-quenching, minimizing measurement errors, and increasing detection sensitivity to a great extent. 35,36 The benzimidazole−Cu complex was synthesized from the reaction of compound BB with CuCl 2 in a 2:1 ratio in the presence of NaH in THF as shown in Scheme 1. The desired product was obtained with high yield and characterized with FT-IR, HR-MS, and UV−vis spectroscopies, as well as elemental analyses.…”
Section: ■ Introductionmentioning
confidence: 99%